The Influence of Green Behavior Innovation on Competitive Advantage in Batik Family Business - Wachjuni, Wachjuni; Novandari, Weni; Setyanto, Refius Pradipta; Sudarto, Sudarto (Asosiasi Dosen Peneliti Ilmu Ekonomi dan Bisnis Indonesia (Adpebi), 2024)
Purpose – This study investigates the impact of green behavior innovation on competitive advantage within Batik SME family businesses, focusing on the influence of emotional intelligence, spiritual intelligence, and green creativity on driving green innovation behavior. Methodology/approach – This study was conducted through a survey research with a quantitative approach, involving 32 Batik SMEs in Indonesia. The testing method employed classical assumption tests, multiple linear regression analysis, and path analysis. Findings – The study finds that Emotional Intelligence positively influences Green Creativity and Green Innovation Behavior, while Spiritual Intelligence has a negative impact on Green Creativity but a positive effect on Green Innovation Behavior. Additionally, Green Creativity plays a crucial role in driving Green Innovation Behavior within family businesses. The findings highlight the significance of Emotional Intelligence and Green Creativity in promoting sustainable practices in Batik SME family businesses Novelty/value – The novelty and value of this research lie in its exploration of the interplay between emotional intelligence, spiritual intelligence, green creativity, and green innovation behavior within Batik SME family businesses in Indonesia. These findings offer a unique perspective on how emotional and spiritual intelligence, coupled with creativity, can enhance competitive advantage and sustainability in the Batik industry.